2017
DOI: 10.2110/jsr.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and Lateral Submarine Lobe Fringes: Comparing Sedimentary Facies, Architecture and Flow Processes

Abstract: 13Submarine lobe fringe deposits form heterolithic successions that may include a high proportion of 14 hybrid beds. The identification of lobe fringe successions aids interpretation of paleogeographic 15 setting and the degree of basin confinement. Here, for the first time, the sedimentological and 16 architectural differences between frontal and lateral lobe fringe deposits are investigated. Extensive 17 outcrop and core data from Fan 4, Skoorsteenberg Formation, Karoo Basin, South Africa, allow the 18 rates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
152
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 116 publications
(159 citation statements)
references
References 92 publications
7
152
0
Order By: Relevance
“…6). This variation is also documented in the Tanqua depocenter (Rozman, 2000;Prélat et al, 2009;Groenenberg et al, 2010) and is interpreted to relate to differences in flow processes in distal frontal versus distal lateral run outs (Spychala et al, 2017b).…”
Section: Discussion Units A/b B/c and D/ementioning
confidence: 62%
See 2 more Smart Citations
“…6). This variation is also documented in the Tanqua depocenter (Rozman, 2000;Prélat et al, 2009;Groenenberg et al, 2010) and is interpreted to relate to differences in flow processes in distal frontal versus distal lateral run outs (Spychala et al, 2017b).…”
Section: Discussion Units A/b B/c and D/ementioning
confidence: 62%
“…Beds with similar thickness, grain size, and sedimentary structures are grouped into facies. Facies are used to interpret environments of deposition within the context of extensive paleoenvironmental reconstructions already undertaken in the Laingsburg depocenter (e.g., Grecula et al, 2003;Figueiredo et al, 2010Figueiredo et al, , 2013Di Celma et al, 2011;Flint et al, 2011;Van der Merwe et al, 2014;Spychala et al, 2015Spychala et al, , 2017aSpychala et al, , 2017bBrooks et al, 2018b). A physical correlation framework was established by walking out stratigraphic surfaces between sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the deposits of a range of composite and transitional flow types, the origin of which is in many cases related to distal flow transformations whereby turbulence is damped and flows with a component of turbulent grain suspension evolve to those with variable cohesion. These types of beds are often relatively mud‐rich and are commonly encountered in the outer and marginal parts of deep‐water systems (Talling et al ., ; Barker et al ., ; Southern et al ., ; Fonnesu et al ., ; Spychala et al ., ). Event beds of this type described in the literature include slurry flows (Lowe & Guy, ; Lowe et al ., ), cogenetic turbidite–debrite beds (Haughton et al ., ; Talling et al ., ), hybrid event beds (HEBs; Haughton et al ., ), transitional flow deposits (Kane & Pontén, ) and matrix‐rich beds (Terlaky & Arnott, ).…”
Section: Introductionmentioning
confidence: 99%
“…Work in South Africa by Hodgson () and Spychala et al . () showed that HEBs in the Permian‐aged Tanqua Karoo Basin were common in lobe fringe deposits formed during the onset of fan initiation cycles and during fan growth.…”
Section: Introductionmentioning
confidence: 99%